MENINGKATKAN KEMAMPUAN BELAJAR DAN MOTIVASI SISWA DALAM MEMBUAT JURNAL UMUM DENGAN MENGGUNAKAN METODE KOOPERATIF LEARNING (BERPASANGAN) - Zuroidah, Ifta (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2016)
This study aims to improve learning ability and motivation to create a general ledger using cooperative learning methods (in pairs). The subjects were students of class XI IPS 4 SMA Muhammadiyah 2 Sidoarjo totaled 39 students. Learning implemented using cooperative learning methods (in pairs). Collecting data using observation observer motivasai teacher and student observation and assessment rubrics. The results showed that the use of methods of cooperative learning (pairs) performed by: dividing the students into groups of pairs consisting of two people, Dividing worksheets to work together, students work with a discussion with his partner, Gathering the work that has been completed, can improve results learning and student motivation.